Risk Management At The Agency Inspectorate XYZ - Nurlinda Dewi Kusumah; Lukman Mohammad Baga; Popong Nurhayati (International Journal of Social Service and Research, 2021)
Risk management in the government environment is currently still not implemented effectively in all government institutions, including the XYZ Agency Inspectorate. Whereas risk management is able to assist the government in achieving its goals and there are regulations to implement it, namely Government Regulation no. 60 of 2008. This study aims to analyze the application of risk management at the XYZ Agency Inspectorate. The benefit of conducting this research is that it can provide management with an understanding of the results of the risk management portrait so that it can decide on the treatment of risks that have the potential to threaten the achievement of activity objectives. Qualitative research methods are carried out through literature studies, normative studies and prospective studies. The method used in this research is a qualitative approach with descriptive analysis research type. The results obtained from this study are that the implementation of risk management in the XYZ Agency's Inspectorate has not been optimally carried out because it is still using the XYZ Agency's risk management standards.